The Critical Discourse Analysis of Content Pedagogy in The Indonesian EFL Textbook: The Alignment with Kurikulum Merdeka - Islamy, Firsty Twentieth Januar; Kristiawan, Dana Yudha; Rahman, Abd. (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This study aims to critically analyze the pedagogical representation in the Indonesian EFL textbook "Bahasa Inggris: Work in Progress" to assess its alignment with the learner-centered and transformative principles of Kurikulum Merdeka, focusing on how it shapes learner roles and pedagogical approaches. This qualitative descriptive study uses Critical Discourse Analysis (CDA) based on Fairclough's (1995) three-dimensional model and content analysis. It examines textual, visual, and task design components of the "Bahasa Inggris: Work in Progress" textbook for Grade X, published in 2021. The textbook partially aligns with Kurikulum Merdeka, incorporating progressive elements like contextualized themes and multimodal resources. However, tasks often remain scripted, limiting autonomy and critical thinking. Visuals are illustrative rather than interrogative, and multimodal activities are peripheral, hindering full realization of transformative ideals. This research is useful for textbook developers, English as a Foreign Language (EFL) educators, and policymakers in Indonesia. It can inform material design, curriculum development, and pedagogical practices within language education, particularly concerning the implementation of Kurikulum Merdeka. This study uniquely combines Critical Discourse Analysis and multimodal analysis to evaluate an Indonesian EFL textbook under Kurikulum Merdeka. It advances existing knowledge by highlighting the tension between progressive curriculum goals and traditional material design, offering specific insights for future textbook revisions